Enhancing the signal contrast ratio and stability of liquid crystal-based sensors by using fine grids made by photolithography of photoresists. Issue 12 (29th April 2021) - Chang, Jung-Jung; Huang, Jhih-Wei; Lin, Chun-Feng; Liu, Shun-Wei; Chen, Chih-Hsin
Abstract : We prepared fine grid patterns on a glass substrate through photolithography of photoresists; we filled photoresist grids with liquid crystals (LCs) to construct LC-based sensors. Abstract : We prepared fine grid patterns on a glass substrate through photolithography of photoresists; we filled photoresist grids with liquid crystals (LCs) to construct LC-based sensors. Scanning electron microscopy images revealed that the photoresist grids were flat, smooth, and 3.0–8.0 μm thick. In contrast to conventional LC-based sensors, in which LCs are filled in metal grids placed on glass substrates, our results proved that LC-based sensors constructed using photoresist grids exhibited a larger signal contrast ratio, better signal stability in aqueous solutions and lower limit of detection for mercuric ions. All these characteristics enhanced the performance of the LC-based sensors.